Luhmann explained from souls to systems - Moeller, Hans-Georg 1964- (Ideas explained series, 2006)
"An introduction to Niklas Luhmann's social systems theory. Discusses key concepts and relevant philosophical issues, and presents a case study. English-language translations of three of Luhmann's essays and bibliographies of works by and on Luhmann are included"--Provided by publisher.